Thermal Ablation of Benign Thyroid Nodules and Papillary Thyroid Microcarcinoma - Bo, Xiao-Wan; Lu, Feng; Xu, Hui-Xiong; Sun, Li-Ping; Zhang, Kun (Frontiers in Oncology, 2020)
Due to the increasing rates of physical examination and application of advanced ultrasound machines, incidences of benign thyroid nodules (BTNs) and papillary thyroid microcarcinoma (PTMC) were dramatically up-regulated in recent years. Thermal ablation (TA) has been widely used and regarded as a safe and effective method to eliminate or reduce BTNs and recurrent low risk PTMC. However, conclusions for TA to treatment of primary PTMC are controversial. Recently, several long-term and prospective studies on TA for thyroid nodules have been reported. Here, we review current literatures and progress on TA for BTNs and PTMC and the way to get the best treatment outcomes, providing a comprehensive view for the research progresses in this field.